Nonsense and sense suppression abilities of original and derivative Methanosarcina mazei pyrrolysyl-tRNA synthetase-tRNA(Pyl) pairs in the Escherichia coli BL21(DE3) cell strain. - Keturah A Odoi; Ying Huang; Yohannes H Rezenom; Wenshe R Liu (PLoS ONE, 2013)
Systematic studies of nonsense and sense suppression of the original and three derivative Methanosarcina mazei PylRS-tRNA(Pyl) pairs and cross recognition between nonsense codons and various tRNA(Pyl) anticodons in the Escherichia coli BL21(DE3) cell strain are reported. tRNA(CUA)(Pyl) is orthogonal in E. coli and able to induce strong amber suppression when it is co-expressed with pyrrolysyl-tRNA synthetase (PylRS) and charged with a PylRS substrate, N(ε)-tert-butoxycarbonyl-L-lysine (BocK). Similar to tRNA(CUA)(Pyl), tRNA(UUA)(Pyl) is also orthogonal in E. coli and can be coupled with PylRS to genetically incorporate BocK at an ochre mutation site. Although tRNA(UUA)(Pyl) is expected to recognize a UAG codon based on the wobble hypothesis, the PylRS-tRNA(UUA)(Pyl) pair does not give rise to amber suppression that surpasses the basal amber suppression level in E. coli. E. coli itself displays a relatively high opal suppression level and tryptophan (Trp) is incorporated at an opal mutation site. Although the PylRS-tRNA(UCA)(Pyl) pair can be used to encode BocK at an opal codon, the pair fails to suppress the incorporation of Trp at the same site. tRNA(CCU)(Pyl) fails to deliver BocK at an AGG codon when co-expressed with PylRS in E. coli.